2021
DOI: 10.1063/1.5142186
|View full text |Cite
|
Sign up to set email alerts
|

On the modified logarithmic Sobolev inequality for the heat-bath dynamics for 1D systems

Abstract: The mixing time of Markovian dissipative evolutions of open quantum manybody systems can be bounded using optimal constants of certain quantum functional inequalities, such as the modified logarithmic Sobolev constant. For classical spin systems, the positivity of such constants follows from a mixing condition for the Gibbs measure, via quasi-factorization results for the entropy. Inspired by the classical case, we present a strategy to derive the positivity of the modified logarithmic Sobolev constant associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In this section, we prove our main results concerning approximate tensorization of the relative entropy (also known in the literature as quasi-factorization [10], [6], [2]). In particular, we relate the weak and strong constants to properties of the subalgebras.…”
Section: A Technical Lemmamentioning
confidence: 74%
See 2 more Smart Citations
“…In this section, we prove our main results concerning approximate tensorization of the relative entropy (also known in the literature as quasi-factorization [10], [6], [2]). In particular, we relate the weak and strong constants to properties of the subalgebras.…”
Section: A Technical Lemmamentioning
confidence: 74%
“…when all algebras are commutative), and when M ≡ C1 H [10]. These inequalities, termed as approximate tensorization of the relative entropy (also known in the literature as quasi-factorization of the relative entropy, [10], [6], [2]), take the following form…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the Gibbs sampler depends on the time it takes to reach the approximating state. In the recent years, various Gibbs samplers were proposed in the literature [44,14,8,19,7]. In [53,65,29], the authors prove curvature lower bounds for different Gibbs samplers and Lipschitz constants.…”
Section: Group Transferencementioning
confidence: 99%
“…Proofs of LSI/MLSI for quantum interacting spin systems (a.k.a. Gibbs samplers) have recently attracted the attention of the community [6,7,2]. More recently, it was shown that Gibbs states over arbitrary graphs satisfy a transportation cost inequality at large enough temperature [21].…”
Section: Gibbs Samplersmentioning
confidence: 99%